2021
DOI: 10.31234/osf.io/nax75
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Day-to-Day Variation in Students’ Academic Success: The Role of Self-Regulation, Working Memory, and Achievement Goals

Abstract: Self-regulation has been shown to be positively associated with school performance. Additionally, interrelations between self-regulation, working memory (WM), and achievement goals, in particular learning goals, have been established, as well as their associations with academic outcomes. It stands to reason that self-regulation, WM, and achievement goals are related on a day-to-day level, with implications for daily and long-term academic success. However, previous research largely considered between-person di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Some children are particularly impulsive when it comes to schoolwork, while others show self-regulation deficits in social interactions. Thus, for some children in our study, fluctuations in self-regulation might have mainly affected the academic domain (i.e., lower academic success on days of low self-regulation; Blume et al, 2022), while for other children, such fluctuations might have predominantly affected interpersonal behavior (i.e., talking back to the parent on days with lower self-regulation). Second, deficits in children’s self-regulation challenge parents to put additional effort into helping their children achieve their goals (i.e., helping out with their homework), which might be particularly difficult for parents with low executive control (Deater-Deckard et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Some children are particularly impulsive when it comes to schoolwork, while others show self-regulation deficits in social interactions. Thus, for some children in our study, fluctuations in self-regulation might have mainly affected the academic domain (i.e., lower academic success on days of low self-regulation; Blume et al, 2022), while for other children, such fluctuations might have predominantly affected interpersonal behavior (i.e., talking back to the parent on days with lower self-regulation). Second, deficits in children’s self-regulation challenge parents to put additional effort into helping their children achieve their goals (i.e., helping out with their homework), which might be particularly difficult for parents with low executive control (Deater-Deckard et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…As the first of its kind, this study aimed to investigate school children’s self-regulation in association with parent-child interaction quality in everyday life, considering daily self-regulation fluctuations in children (e.g., Blume et al, 2022; Ludwig et al, 2016). The use of ambulatory assessment across several days within 13 months allowed us to reliably capture between-person differences, as well as day-to-day within-person variations in children’s self-regulation within shorter time frames (i.e., on a day-to-day basis) and across a longer developmental period (i.e., within one school year).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blume et al. (2022) implemented two studies to address the relations of daily SR, working memory (WM), and achievement goals, and their relevance for daily and general academic success. Study 1 results indicated that daily performance‐approach goals and SR, but not other goals or WM uniquely, contributed to daily perceived academic success.…”
mentioning
confidence: 99%